A Rare Prostatic Diagnosis of an Old Man: A Pure Prostatic Leiomyoma. (24th August 2013) - van Ulden-Bleumink, W. M.; Dom, P. G. B.; Ramakers, B. P. M.; van Adrichem, N. P. H.
Abstract : A pure leiomyoma of the prostate is a rare benign tumor. An 82-year-old man was referred to our urology department with gross hematuria and complete urinary retention. Examination revealed a benign prostatic hyperplasia. Transrectal ultrasound showed a prostate of 125 mL. Serum PSA was 1.9 µg/L. A simple retropubic prostatectomy was performed. Histopathological examination showed a pure leiomyoma of the prostate, without the presence of glandular prostate tissue. The diagnosis, characteristics, and treatment of this tumor are described.